Solvent cleaning and wettability of technical steel and titanium surfaces - Stefan Becker; Rolf Merz; Hans Hasse; Michael Kopnarski (Adsorption Science & Technology)
The ability of the cleaning agents such as cyclohexane, acetone, isopropanol and hydrogen peroxide to remove oil from technical steel and titanium samples was studied in systematic experiments. The composition of the organic residues and the layer thickness on the differently cleaned surfaces were determined via X-ray photoelectron spectroscopy analysis, and the corresponding water contact angles were measured. The ability of the cleaning agents to remove oil was found to increase in the following order: acetone, isopropanol, cyclohexane and hydrogen peroxide. The relationship between the chemical composition of the residues and the observed contact angles is investigated, and a quantitative correlation is developed.